Pengaruh Fasilitas, Kualitas Pelayanan, Dan Lokasi Terhadap Kepuasan Pengguna Jasa Pada Kantor Pengawasan Dan Pelayanan Bea Dan Cukai Tipe Madya Pabean Tanjung Emas Semarang - Maula Famungka; Ida Martini Alriani (Universitas Katolik Widya Karya Malang, 2023)
The purpose of this study was to find out about the effect of facilities, service quality, and location on service user satisfaction at the Customs and Excise Service Office of the Middle Type Tanjung Emas Semarang. The population used is all service users of the Customs and Excise Supervision and Service Office (KPPBC) of the Tanjung Emas Middle Type Customs Office, Semarang. which amounted to infinity. Determination of this sample using accidental sampling technique. The number of samples used in this study were 40 service users. This research data analysis tool uses multiple linear regression. The results of the study show that facilities have a positive effect on service user satisfaction. This is indicated by the calculated t value that is greater than t table, namely 3.092> 1.688, with a sig. of 0.000 <0.05 (significant). Service quality has a positive effect on service user satisfaction. This is with a calculated t value of 3.913 > 1.688, with a sig. of 0.000 <0.05 (significant). Location has a positive effect on service user satisfaction. This is indicated by the t-value which is negative, namely 7.396> 1.688, with a sig. of 0.000 <0.05 (significant).